Violet Emission of ALD‐Grown ZnO Nanostructures on Confined Polymer Films: Defect Origins and Emission Control via Interface Engineering Based on Confinement of the Bottom Polymer Template. Issue 5 (7th February 2019) - Mathur, Aakash; Pal, Dipayan; Singh, Ajaib; Sengupta, Amartya; Singh, Rinki; Chattopadhyay, Sudeshna
Abstract: ZnO thin films on polymer templates (polystyrene, PST) show strong influence of the interface via degree of confinement of the bottom polymer template in introducing the controlled defect levels in the ZnO nanostructures and consequently yield significant variation at room temperature photoluminescence (PL). The thickness of the polymer thin film in terms of its radius of gyration ( R g ) defines the degree of confinement of PST. Simultaneous growth of ZnO thin films by atomic layer deposition (ALD) with 150 cycles at 35 °C on spin‐coated polystyrene (PS) films of different thicknesses forms sets of ZnO/PST hybrid systems. The ZnO thin film exhibits a distinct/unusual violet emission (2.95 eV) along with the common near‐band‐edge and green emissions, when it grows on 6.5 R g PST. Such defect‐induced emissions disappear with increasing degree of confinement of the bottom PST from 6.5 R g to 1.5 R g, and sharper UV peak dominates the PL spectra along with a prominent redshift in near‐band‐edge. Furthermore, with increasing film thickness of the bottom PST template from 1.5 R g to 6.5 R g, the ALD growth rate of ZnO increases by 25%. The study offers new insights into the research on opto‐electronic applications of ZnO thin films in the emerging field of organic electronics. Abstract : The degree of confinement of polystyrene templates (PSTs) alters the interface of the ZnO/PST hybrid system and consequently influences the growth of ZnO thin films, which produces controlled variation in defect levels in ZnO nanostructures and the corresponding substantial changes in the photoluminescence (PL) spectra, indicating its importance in the research on opto‐electronic applications of ZnO thin films in the field of organic‐electronics.